Motherly and feminist reflections in contemporary narratives written by women - Oliveira, Paloma do Nascimento; Oliveira, Tássia Tavares de (Revista Letras Raras, 2021)
The motherhood romanticization works as a means to control the bodies and reproduction in the patriarchal system, making it compulsory: building up the belief that women are only fulfilled after giving birth, also putting the mother's love as a means to exploit the act of caring, something that is not imposed on fathers. Although idealized, real motherhood women complain of exhaustion, solitude and lack of public policies and social support. The feminist movement must face motherhood as fundamental to the movement of freeing women, from the sexual and reproductive rights to the planning and division of tasks and mental overload. Race and social classes are also intertwined, being black women the most common victims of violent acts and their childs victims of violent acts. Contemporary female writers are watchful to these questions and desecrate motherhood in many narratives. This paper has the objective of bringing a feminist reflection about mothering, not faced as something natural and impository to all women, but as a process that involves a series of cultural and political questions, from the reading and discussion of female authors such as Adichie (2017), Collins (2019), hooks (2019 e 2020), Mendonça (2014), D’Ávilla (2019) and Gonzalez (2020) and from a host of narratives from female contemporary authors from Brazil, Canada, Caribbean and African countries like Atwood (2017), Condé (2020), Emecheta (2018), Evaristo (2016), Leite (2004), Luft (2012), Mukasonga (2017), Munro (2014), Ntshingila (2016) and Rezende (2014), which justifies the pertinence of the subject beyond its national borders.